The modulatory role of phloretin in Aβ25–35 induced sporadic Alzheimer’s disease in rat model - Ghumatkar, Priya J.; Patil, Sachin P.; Peshattiwar, Vaibhavi; Vijaykumar, Tushara; Dighe, Vikas; Vanage, Geeta; Sathaye, Sadhana (Naunyn-Schmiedeberg's archives of pharmacology, 2019)
Alzheimer’s disease (AD) is the leading neurodegenerative disorder with extracellular senile plaques and neurofibrillary tangles as the major hallmarks. The objective was to evaluate the effect of phloretin in a chronic model of sporadic AD by injecting aggregated form of Aβ25-35 peptide sequence intracerebroventricularly (icv) in Wistar rats. To achieve this, male Wistar rats were injected with aggregated Aβ25-35 peptide icv, followed by 21 days phloretin (2.5 mg/kg, 5 mg/kg) administration after recovery period. Barnes maze and elevated plus maze along with the biochemical estimation of antioxidant enzymes activities were conducted. The hippocampus region of the rat brains were stained with Congo red and Nissl stain. TNF-α was estimated in the brain homogenates using the ELISA assay. In this study, phloretin improved the spatial memory formation and retention in Barnes maze test. Additionally, phloretin alleviated the antioxidant defense biomarkers and thereby reduced oxidative stress, decreased TNF-α-mediated neuroinflammation. Furthermore, phloretin treatment showed decreased amyloid beta accumulation in the CA1 region and less number of pyknotic nuclei in the dentate gyrus of the Aβ25-35-injected rat brains. The above experimental findings evinced the promising role of phloretin in Aβ25-35-injected rats and which further envisage its potential to be explored in the treatment of AD.